(untitled) (Research, Society and Development, 2020)
The aim of this study was was to determine the nutritional requirements of digestible methionine+cystine (M+C) for white-egg layers aged one to six weeks. A completely randomized design with five methionine+cystine levels, six replicates, and 30 birds per experimental unit was adopted. Dietary treatments consisted of five diets supplemented with DL-Methionine with resulted in five levels of digestible methionine + cystine, 80% (0.516%), 90% (0.578%), 100% (0.640%), 110% (0.702%), and 120% (0.764%), based on Brazilian tables of nutritional requirements. Performance, serological blood, and histological data were evaluated. Feed intake, feed conversion, hepatic glycogen deposition, enzymatic activity of alanine aminotransferase and gamma-glutamyl transferase, and serum creatinine and albumin levels had showed a quadratic response to the levels of digestible M+C, with the respective requirements: 89.78% (0.575%), 114.33% (0.732%), 86.50% (0.554%), 100% (0.640%), 100.40% (0.643%), 104.30% (0.668%), and 111.88% (0.716%). Increasing levels of methionine+cystine elevated the relative liver weight and the deposition of hepatic glycogen, in addition to promote higher growth in pullets, with better body weight and body weight gain and feed conversion ratio. Our findings suggest that 0.732% digestible methionine+cystine is recommended, which corresponds to an intake of 151.20 mg/bird/d and a Met+Cys:Lys ratio 83%, for light pullets from one to six weeks.